Genomic and morphological study of four different varieties of patchouli plant - Vinisha, Mehanathan (2025)
Pogostemon cablin, also known as the patchouli plant, is one of the most economically important species in the essential oil industry because of its aromatic properties and diverse applications. This research focusses on the genomic and morphological characteristics of four distinct varieties of Pogostemon cablin: Sri Makmur, Paya Rambutan, Jerantut, and Kuala Pilah. These varieties were tested to gain a better understanding of their phenotypic and genetic diversity, as well as to investigate potential applications in industry and agriculture. The researchers used a multidisciplinary approach that included physical morphology analysis, scanning electron microscopy (SEM), and whole genome sequencing (WGS). Physical morphological studies revealed significant differences in leaf size, shape, margin characteristics, and trichome density, as well as variations in stem and root structure between varieties. SEM analysis revealed detailed information about trichome types, stomata, and other epidermal features that are important for essential oil production. Genetic analysis using WGS provided insights into genomic architecture and highlighted genetic variations that underpin the observed morphological diversity. The findings help to provide a comprehensive understanding of Pogostemon cablin's genetic and phenotypic variability. This knowledge has important implications for the selection and cultivation of high-yielding patchouli varieties with desirable characteristics, particularly in the essential oil industry. Furthermore, the study emphasises the potential of genomic tools to improve breeding programs and conservation strategies for this economically important species. By integrating morphological and genomic data, this research establishes the groundwork for future studies aimed at optimizing patchouli cultivation and advancing its commercial applications.